A review on phase change materials for thermal energy storage in buildings: Heating and hybrid applications. (January 2021) - Faraj, Khaireldin; Khaled, Mahmoud; Faraj, Jalal; Hachem, Farouk; Castelain, Cathy
Highlights: State-of-the-art review on PCM building applications for heating and hybrid systems. Active and Passive classification for heating and hybrid systems. Challenges altering the PCM technology for energy-efficient buildings are addressed. Hybridization of active and passive systems forms a potential method toward NZEB. Abstract: Researchers world-wide are investigating thermal energy storage, especially phase change materials, for their substantial benefits in improving energy efficiency, sustaining thermal comfort in buildings and contributing to the reduction of environmental pollution. Residential buildings and commercial constructions, being dependent on heating and cooling systems, are subjected to the utilization of PCM technology through several applications. The current study presents a state-of-the-art review that covers recent literature on thermal energy storage systems utilizing PCMs for buildings. The reviewed applications are heating and hybrid applications, that are categorized as passive and active systems. A summary of the PCMs used, applications, thermo-physical properties and incorporation methods are presented as well. The study emphasizes the promising effectiveness of PCM in building heating applications, and highlights the significance of PCM system hybridization. The study shows that experimental investigations on commercial constructions, and hybrid systems development and optimization, are still required. Finally, possible combinations of active and passive heating applications with their auspicious benefits in terms of energy efficiency augmentation, are recommended.